2015
DOI: 10.5826/dpc.0502a22
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced basal cell carcinoma

Abstract: Background: The treatment of tinea capitis using radiotherapy was introduced at the beginning of the twentieth century. A variety of cancers including basal cell carcinoma (BCC) are seen years after this treatment. Objective: We sought to determine the clinical characteristics of BCCs among irradiated patients. Methods: The clinical records of all patients with BCC in a clinic in north of Iran were reviewed. Results: Of the 58 cases of BCC, 29 had positive history for radiotherapy in their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In the literature, an often pigmented nodular appearance has been reported, which is specific to both primary and radio-induced BCCs. 4,14 All the authors agree that BCC is the predominant histological type for both radiation-induced skin tumours and primary skin tumours. 5,9,[12][13][14] Our series nevertheless reported a good number of squamous cell carcinomas, that is, 25 lesions in 20 patients (12•5%).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In the literature, an often pigmented nodular appearance has been reported, which is specific to both primary and radio-induced BCCs. 4,14 All the authors agree that BCC is the predominant histological type for both radiation-induced skin tumours and primary skin tumours. 5,9,[12][13][14] Our series nevertheless reported a good number of squamous cell carcinomas, that is, 25 lesions in 20 patients (12•5%).…”
Section: Discussionmentioning
confidence: 86%
“…4,14 All the authors agree that BCC is the predominant histological type for both radiation-induced skin tumours and primary skin tumours. 5,9,[12][13][14] Our series nevertheless reported a good number of squamous cell carcinomas, that is, 25 lesions in 20 patients (12•5%). We have even reported cases of adnexal tumours.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…2,6,8,9 Post-radiotherapy BCCs are often multiple and typically occur after a long latency period, usually of several decades. [2][3][4]6 It has also been described that BCCs of the scalp arising in this setting demonstrate more aggressive behaviour, with a higher rate of recurrences, often demanding more aggressive surgical excision, 10 although this assertion has been challenged due to methodological issues. 11 Another study found that, despite a high proportion of histologically aggressive cases, there was no apparent aggravation of their biological behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with a history of radiation treatment, the prevalence of BCC is higher than in patients with no history of radiation treatment [7][8][9]. Moreover, several reports have characterized radiogenic BCC as gen-erally more aggressive, difficult to excise completely, and more likely to recur than non-radiogenic BCC [9,10]. Therefore, it is important to conduct a close physical examination, especially of areas previously exposed to radiation, in patients with a history of radiation treatment [7][8][9]11].…”
Section: Introductionmentioning
confidence: 99%